2013
DOI: 10.14419/ijet.v3i1.1478
|View full text |Cite
|
Sign up to set email alerts
|

Study of mosquito attractants for photo catalytic mosquito trap

Abstract: Photo catalytic mosquito trap is made of TiO 2 -Activated Carbon (AC) with a certain composition of AC. Research concerns on the heat spectrum which is produced by combination process of existing CO 2 and humid air. The purpose of performance testing is to observe capability of this device in trapping mosquitoes related to the air temperature profile for heat spectrum is play important role for attracting mosquitoes. Result shows photo catalytic mosquito trap is more effective than devices which only consist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This action would reduce the water vapor as mosquito attractant. 23 Another study reported that coconut oil-derived fatty acid also showed even better repellent activity than DEET. 24 In contrast, another study reported that soybean oil itself had no repellent activity but only supported other repellent's effectivity.…”
Section: Discussionmentioning
confidence: 99%
“…This action would reduce the water vapor as mosquito attractant. 23 Another study reported that coconut oil-derived fatty acid also showed even better repellent activity than DEET. 24 In contrast, another study reported that soybean oil itself had no repellent activity but only supported other repellent's effectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Host-attractant baited traps and targets are some of the promising environmentally friendly technologies currently being considered for mosquito control since the beginning of the last decade [15,28,29]. Volatile attractive host odor has been recognized to play an important role in guiding malaria vectors to the human host and preferred feeding site(s) [15,16,24,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%